Preparation of Ce0.65Zr0.35O2 by co-precipitation： The role of hydrogen peroxide - 黄利华 陈山虎 朱艺 龚茂初 陈耀强 (Journal of rare earths, 2013)
The effect of H2O2 on the properties of Ce0.65Zr0.35O2 a mixed aqueous solution of ammonia and was explored by treating cerium nitrate and zirconium nitrate with in the presence/absence of H2O2. The resultant products were characterized by X-ray diffraction （XRD）, X-ray photoelectron spectroscopy （XPS）, nitrogen adsorption/desorption, oxygen storage capacity （OSC） and H2- reduction （H2-TPR）. The presence of H2O2 was found to have profound effect on powder properties such as surface area, crystallite size of the samples. It was also shown that the addition of H2O2 favored the incorporation of Zr4＋ into CeO2 lattice, which facilitated the formation of CeO2-ZrO2 solid solution, and enhanced the thermal stability of the samples. OSC and H2-TPR studies indicated that the use of H2O2 enhanced the OSC and redox properties. Catalytic activity tests showed that as a support, the Ce0.65Zr0.35O2 prepared in the presence of H2O2 was more suitable for three-way catalyst. The corresponding Pd-only three-way catalyst demonstrated outstanding performance： wide air to fuel operation window, low light-off and total conversion temperature for the conversion of C3H8, NO and CO.